Unlocking hematopoietic stem cell potential: integrative computational approaches for genomic and transcriptomic analysis - Raghav, Pawan Kumar; Banerjee, Basudha; Chadha, Rajni (Frontiers in Cell and Developmental Biology, 2025)
Hematopoietic stem cells (HSCs) sustain lifelong hematopoiesis through their capacity for self-renewal and multilineage differentiation. However, the isolation and functional characterization of HSCs remain challenging due to their cellular heterogeneity and dynamically regulated transcriptional and epigenetic landscapes. Advances in experimental and computational biology, including single-cell RNA sequencing (scRNA-seq), chromatin immunoprecipitation sequencing (ChIP-seq), network inference algorithms, and machine learning, have improved our ability to resolve transcriptional states, trace lineage trajectories, and reconstruct gene regulatory networks (GRN) at single-cell resolution. These approaches enable the discovery of novel HSC subtypes and regulatory factors, and facilitate the integration of multi-omics data to uncover epigenetic and transcriptional mechanisms that drive stem cell fate decisions. Additionally, machine learning models trained on high-throughput datasets provide predictive power for identifying novel enhancers, transcription factors, and therapeutic targets. This review underscores the synergistic role of computational tools in deciphering HSC biology and highlights their potential to improve stem cell therapies and precision treatments for hematologic disorders.